En jämförande studie av fluiddynamiken för olika fluidiseringsmedium i en kallmodell av en 100 kW-anläggning för kemcyklisk förbränning - ANDERSSON, MIKAELA; FRÄNDBERG, SOFIA; JOHANSSON, DAVID; KARLBRINK, MALIN; ROLEN, ALEXANDRA (My University, 2013)
To reduce emissions of carbon dioxide (CO2) Carbon Capture and Storage (CCS) technologies have been developed. Chemical Looping Combustion (CLC) is a CO2 capture technology with the CCS framework, and at Chalmers University of Technology in Gothenburg, Sweden, a 100 kW chemical looping combustor has been built. This project aimed to investigate to what degree air can replace helium as the uidizing gas for uid dynamical studies in a CLC cold ow model of the above mentioned 100 kW facility. Experiments were performed using air and helium separately as uidizing gas and pressure data were obtained, which formed the basis for the comparison. The project also aimed to investigate uid dynamics in the uidized bed and study when the risk of slugging occuring was greatest. The results were presented in the form of figures and tables divided into pressure, concentration and standard deviation of the pressure. The results obtained showed that air as uidizing gas did not create the same uid dynamics as helium over the entire fuel reactor. The magnitude of the deviation varied in the various segments of the reactor. Results obtained regarding slugging in the fuel reactor showed that the risk of slugging occuring increased with increasing uidization velocity. The risk was greatest for velocities between 0.7-1.1 m/s. The results also showed that there was a greater risk of slugging occuring when helium was used as uidizing gas.
Keywords: Energi; Kemiska processer; Energy; Chemical Process Engineering